Peran Physical Health dan Work-life Balance terhadap Psychological Well-being dengan Work-stress sebagai variabel intervening pada Karyawan PT X di Bekasi - Nugraha, Delaja Samuel; Mulya Virgonita I. Winta (Universitas Semarang, 2025)
This study aims to analyze the role of Physical Health and work-life balance on psychological well-being and work-stress at PT X employees in Bekasi. The population in this study were 126 employees of PT X in Bekasi. Sampling in this study is using saturated sampling. The research data were collected using three scales, namely the Physical Health scale, the work-life-balance scale, and the psychological wellbeing scale. Data analysis was performed using SEM PLS. The test results show that Physical Health and Work-life Balance partially have a significant effect on Work-stress with a p-value of 0.025 and a p-value of 0.000. Work-stress has a significant effect on Psychological Well-being with a p-value of 0.001. Physical Health has no significant effect on Psychological Well-being with p-values of 0.388 or more than 0.05. Work-life balance has a significant effect on Psychological Well-being with a p-value of 0.000. Physical Health has a significant effect on Psychological Well-being with Work-stress as an intervening p-value of 0.038. While Work-Life Balance has a significant effect on Psychological Well-being with Work-stress as an intervening with a p-value of 0.001. In this study, it is proven that work-stress mediates the effect of physical health and work-life balance on psychological well-being.